(untitled) (Research, Society and Development, 2023)
The objective of the study is to implement a remote monitoring tool for earthworks through the Arduino platform and cloud storage. As for methodological procedures, data collection in an earthworks work is still a great difficulty, requiring a number of people and equipment, where all this information is done in many cases manually. This work presents a way to systematize this whole process, collecting data automatically, using the concept of Internet of Things. To make it a reality, prototypes were built, with sensors that can be installed in earthmoving equipment, where they are connected via Wi-Fi, generating important information for a database. The results indicate that the data collected by the RFID sensor, sent to the database via radio communication, were satisfactory, thus being able to adapt it to any equipment to be monitored. It is expected that the techniques developed in this research will be relevant in real-scale use in earthworks.